2014
DOI: 10.4067/s0717-97072014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Reaction Rate Constants of Hydroxyl Radical With Organic Compounds

Abstract: In this work we have performed a QSAR study of atmospheric reactions with hydroxyl radical, at the B3LYP level of theory with 6-31G(d) basis set. Molecular descriptors selected by applying multiple linear stepwise regression (MLR) analysis were used to predict the reaction rate constants (-logk OH ) of OH radicals with organic compounds in the atmosphere, including 98 alkenes and 80 aromatic compounds. For setting our reactions, we have calculated 98 alkenes and 80 aromatic compounds. A four-descriptor MLR mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It is worth noting that the reactivity of aromatic compounds with HO•, a powerful oxidant, and electrophilic species, increases in the presence of hydroxyl substituents, i.e., electron-donor groups, which are present in salicylic acid and paracetamol. On the other hand, electron-withdrawing groups decrease reactivity 19,26,27 . In our study, the carboxylate group in salicylic acid is a strong electron-withdrawing group, and the amide in paracetamol, a moderated one.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the reactivity of aromatic compounds with HO•, a powerful oxidant, and electrophilic species, increases in the presence of hydroxyl substituents, i.e., electron-donor groups, which are present in salicylic acid and paracetamol. On the other hand, electron-withdrawing groups decrease reactivity 19,26,27 . In our study, the carboxylate group in salicylic acid is a strong electron-withdrawing group, and the amide in paracetamol, a moderated one.…”
Section: Resultsmentioning
confidence: 99%
“…Acetophenone is a pollutant, and studies about its photodegradation have been reported 11,31,32 . On the other hand, 4-aminoacetophenone was never studied in this context, but the presence of the amino group makes this compound more susceptible to oxidation and electrophilic attack 19,26 . Therefore, it should be expected 4-aminoacetophenone as more reactive, or at least similar to benzophenone.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid structure simulation and calculations were performed as previously reported [4,19]. Briefly, the molecular structures of lipids were drawn using Chem-BioDraw Ultra 12.0, transferred to the ChemBio3D Ultra 12.0 module, and pre-optimized using the MM2 force field calculation until the minimum rms error was < 0.100 kcal/mol/Å to generate the lowest energy conformation.…”
Section: Structure Simulation and Calculationmentioning
confidence: 99%
“…In addition, Lundstedt et al [27] observed that lowmolecular-weight PAHs and heterocycles degraded more rapidly than the high-molecular-weight compounds and that the presence of alkyl substituents or nitrogen atoms in the aromatic rings reduced the degradation rates. Among derivatives of benzene, those with large alkyl side chains such as tert-butyl or n-propyl that impose more steric hindrance for reaction with Á OH as well as being less thermodynamically stable were predicted to be less reactive than those with smaller and more stable alkyl groups such as methyl, vinyl, and isopropyl [28]. For example, toluene was more reactive than tert-butylbenzene, and styrene was more reactive than ethylbenzene [28].…”
Section: Hydroxyl Radical Rate Constantmentioning
confidence: 99%
“…Among derivatives of benzene, those with large alkyl side chains such as tert-butyl or n-propyl that impose more steric hindrance for reaction with Á OH as well as being less thermodynamically stable were predicted to be less reactive than those with smaller and more stable alkyl groups such as methyl, vinyl, and isopropyl [28]. For example, toluene was more reactive than tert-butylbenzene, and styrene was more reactive than ethylbenzene [28]. Our results are consistent with these predictions.…”
Section: Hydroxyl Radical Rate Constantmentioning
confidence: 99%